Gaya Arsitektur di Kawasan Kota Tua Jalan Gajah Mada, Denpasar - Agreichorna F. B. Sau Sau; I Gusti Ngurah Made Dwi Ana Toya; I Putu Wisnu Adi Setiawan; Ni Wayan Meidayanti Mustika; Putu Gede Wahyu Satya Nugraha (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
The old town area on Jalan Gajah was used as a trading center. This area is motivated by old buildings that functioned as shops. These old buildings are categorized as cultural heritage buildings or heritage buildings in the heritage area of Jalan Gajah Mada which have aesthetic values from both exterior and interior. The buildings in the old city area on Jalan Gajah Mada have various architectural styles. This study aims to determine how the architectural style of the existing buildings in the Gajah Mada street area using a qualitative descriptive method. Data collection is done through direct observation of the object of research. The results showed that the architectural style in the Old Town area of Jalan Gajah Mada applied 3 architectural styles, namely, traditional Balinese, Chinese and Colonial architectural styles. The three architectural styles are unique in each of their respective styles. In the development of Denpasar City, the buildings that still exist are made into cultural heritage or heritage buildings that should be maintained by the architectural style of the building